2021
DOI: 10.3390/ijms221910232
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Targeted Therapy and Immunotherapy for Myelodysplastic Syndrome

Abstract: Myelodysplastic syndrome (MDS) is a heterogeneous, clonal hematological disorder characterized by ineffective hematopoiesis, cytopenia, morphologic dysplasia, and predisposition to acute myeloid leukemia (AML). Stem cell genomic instability, microenvironmental aberrations, and somatic mutations contribute to leukemic transformation. The hypomethylating agents (HMAs), azacitidine and decitabine are the standard of care for patients with higher-risk MDS. Although these agents induce responses in up to 40–60% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 276 publications
0
19
0
Order By: Relevance
“…Together they deliver a potent phagocytic signal to macrophages ( 253 ). Magrolimab is a monoclonal antibody that blocks CD47 to escape immune surveillance and macrophage-mediated clearance ( 254 ). Clinical trials have shown that magrolimab, is safe when administered as monotherapy ( 255 ).…”
Section: Somatic Mutationsmentioning
confidence: 99%
“…Together they deliver a potent phagocytic signal to macrophages ( 253 ). Magrolimab is a monoclonal antibody that blocks CD47 to escape immune surveillance and macrophage-mediated clearance ( 254 ). Clinical trials have shown that magrolimab, is safe when administered as monotherapy ( 255 ).…”
Section: Somatic Mutationsmentioning
confidence: 99%
“…Since MCC is considered an aggressive and deadly tumor, there is an urgent need to identify novel effective therapies for its management. As the malignant behaviour of MCC cells can be reverted with iHDACs ( 17 , 69 , 71 , 72 , 77 ), combination multidrug therapies with hypomethylating agents should be considered ( 45 , 107 , 108 ), as has successfully been demonstrated in treating other tumors ( 109 111 ). We therefore recommend further rigorous preclinical/clinical studies in this direction ( 112 ).…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Finally, we also sought to investigate candidate biomarkers of responsiveness to azacytidine plus venetoclax therapy, and well-established biomarkers (e.g., WT1 mRNA levels or NBC) or other novel molecules were studied, such as Tim-3 expression levels. For example, Tim-3, a checkpoint receptor, is a promising targeted therapy in cancer immunotherapy, and its inhibitor, cobolimab, has displayed efficacy and safety as monotherapy or in combination with other checkpoint inhibitors in patients with advanced solid tumors in phase I AMBER study ( Falchook GS et al, 2022 ), and has been also proposed in high-risk MDS ( Lee P et al, 2021 ). Indeed, Tim-3 expression is increased on blasts and in high-risk hematological diseases ( Asayama T et al, 2017 ), together with its pathway companion, galectin-9, and proliferation of Tim-3 + MDS blasts can be inhibited by anti-Tim-3 antibody ( Gonçalves Silva I et al, 2017 ; Wolf Y et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%